Pengaruh Employer Branding terhadap Minat Kerja Generasi Z pada Perusahaan Digital - Oktavian Tri Pandowo; Yusuf Azka Junianto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the effect of employer branding on the job interest of Generation Z in digital companies. The background of this research is based on the increasing competition among companies in attracting young talents, especially Generation Z, who have unique characteristics such as being highly adaptive to technology, prioritizing work-life balance, and having high expectations toward the workplace environment. Employer branding has become an essential strategy for companies to build an attractive and competitive image as an employer. This study employs a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 100 respondents from Generation Z who are seeking jobs or interested in working in digital companies. The sampling technique used was purposive sampling. Data analysis techniques include validity testing, reliability testing, simple linear regression analysis, and t-test. The results indicate that employer branding has a positive and significant effect on Generation Z’s job interest. This implies that the better the company’s image as an employer, the higher the interest of Generation Z to work in the company. This study suggests that digital companies need to strengthen their employer branding strategies to attract and retain young talents.